Looking Out and Looking In: Exploring a Case of Faculty Perceptions during E-Learning Staff Development - Esterhuizen, Hendrik Daniël; Blignaut, Seugnet; Ellis, Suria (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
This explorative study captured the perceptions of faculty members new to technology enhanced learning and the longitudinal observations of the e-learning manager during dedicated professional development in order to compile a socially transformative emergent learning technology integration framework for open and distance learning at the School of Continuing Teacher Education at North-West University, South Africa. A pragmatic approach guided the bounded case study. The study followed a fully mixed sequential equal status design of mixing sequential qualitative and quantitative findings. Data collection strategies concern a custom-made questionnaire, interviews with faculty members, and longitudinal observations by the e-learning manager. The first phase uncovered 34 qualitative codes. After quantitating of the data, a t-test indicated significant differences for 17 variables between faculty perceptions and observations of the e-learning manager. Ward’s method of Euclidean distances grouped the variables into five clusters according to the researchers’ paradigm of looking in and looking out from the development context. The clusters formed the basis of a model for faculty development towards socially transformative learning technology integration for open distance learning. The five aspects of the model comprise (i) the environment in which faculty members should gain support from the institution; (ii) the environment in which faculty have to address the realities of adopting TEL; (iii) human factors relating to the adoption of TEL; (iv) concerns and reservations about the use of TEL; and (v) continuing professional development needs, expectations, and motivators. The sustainable integration of ICT into higher education institutions remains a major challenge for the adoption of TEL.